A Critical Evaluation of the Ownership and Responsibilities of Early Childhood Care, Development and Education in Sri Lanka - L. Abesooriya (The Open University of Sri Lanka, 2020)
The Early Childhood Care and Development (ECCD) and Education in Sri Lanka have been considered vital for human development (UNICEF, 2007 cited in Gallardo, 2009). Yet, there is less attention paid to the scrutinised formulation of policies related to this aspect in Sri Lanka. Furthermore, child-related studies conducted in Sri Lanka are limited. This paper aims to contribute to this necessity by conducting a critical evaluation regarding the responsibility of the formulation of ECCD and education policies in Sri Lanka. A qualitative research design was used for this study. Thirteen policy documents related to ECCD and education were critically analysed and interviews were conducted with responsible informants of ECCD and education in order to gather data. The findings exhibited that there was no single designated authority that is responsible for the formulation of policies related to ECCD and education in Sri Lanka. Furthermore, it was noted that the responsibility of ECCD and education-related policy formulation constantly shifted from one authority to another. In addition, it was noted that the responsibility regarding the formulation of policies for different aspects of ECCD and education were delegated to different parties. Lack of coordination among these diverse parities had resulted in no clear-cut policies for any of the aspects of ECCD and education. Furthermore, lack of supervision and monitoring had resulted in the non-implementation of the prevalent ECCD and education policies in Sri Lanka. Hence, the requirement for stern and stable ECCD policy formulating and monitoring agents is highlighted in the present study.